IMPACT OF RESISTANCE EXERCISE ON NEUROCOGNITIVE HEALTH AND SARCOPENIA IN THE ELDERLY - Sebastian Polok; Małgorzata Wasilewska; Krzysztof Pietrzak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Sarcopenia (progressive muscle loss/weakness) and neurocognitive decline are serious, interrelated difficulties of aging, with shared pathophysiological pathways including inflammation and disrupted muscle-brain communication. Resistance exercise training (RET) counters sarcopenia and additionally may be beneficial for cognition via myokine release.Methods: Systematic review (PubMed/Google Scholar) of the impact of RET on sarcopenia and neurocognitive health in adults aged ≥ 65 years was done. The search words were "resistance exercise", "sarcopenia", "neurocognitive health", and "elderly". Clinical studies, trials, meta-analyses, and RCTs after 2017 were included. After screening 348 records and applying exclusion criteria, 21 studies were analyzed.Results: RET significantly improves sarcopenia, increasing muscle strength (e.g., knee extension SMD=1.26), mass (especially with protein supplementation), and physical function (e.g., gait speed SMD=1.28), reducing fall risk. RET also yields domain-specific cognitive improvements, most consistently in executive function and processing speed, that are coupled with hippocampal expansion and expanded functional connectivity. RET elevates neurotrophic factors (e.g., BDNF) and reduces inflammation (e.g., IL-6). Crucially, several studies demonstrate concurrent improvements in both cognition and muscle strength/function, with strength improvement being related to cognitive improvement (up to 40% mediation).Discussion: RET provides two-fold protection through mechanisms like heightened protein synthesis, reduced inflammation, and neurotrophic support. Barriers include low adherence, access, and standardization of protocols (e.g., optimal dose: ≥2 sessions/week, 70–80% 1RM). Future research needs validated biomarkers, optimized protocols (including nutritional co-interventions), and high-quality RCTs on minimal effective doses and synergies.Conclusions: RET is a robust, evidence-based intervention counteracting both sarcopenia and cognitive impairment in older adults, and promoting functional independence and healthy aging. The resolution of implementation concerns and outstanding research questions is necessary to maximize its public health impact.